Realizing ultra-high strength and excellent ductility in a low-alloyed biomedical Mg-Zn-Ca-MgO composite - Chaokun Tang; Shaoyuan Lyu; Ruixiao Zheng; Guodong Li; Zhongyang Liu; Minfang Chen; Bin Jiang (Journal of Magnesium and Alloys)
An ultra-fine grained (UFG) Mg-1Zn-0.2Ca-1.0MgO composite with an average grain size of 0.49 µm as well as an excellent combination of yield strength (379 MPa) and ductility (10.1%) was produced by one-step extrusion. Subsequent heat treatment at 200 ℃ for 30 min further improved its yield strength to 420 MPa and elongation to 12.1% with a slight grain growth to 0.76 µm. Microstructure observations revealed that the precipitation of high number density of Ca2Mg6Zn3 phase was the main reason for the enhanced strength after ageing treatment. Grain coarsening and recovery of dislocations during ageing improved the work-hardening capability of the extruded sample, leading to improved ductility. Our work provides a pathway for the mass production of strong and ductile Mg-based materials without excessive addition of alloying elements.